Experiences of occupational therapy education: contexts, communities and social occupational therapy/ Experiências de formação em terapia ocupacional: contextos, comunidades e terapia ocupacional social - Irvine-Brown, Laura; Di Tommaso, Amelia; Malfitano, Ana Paula Serrata; Molineux, Matthew (Cadernos Brasileiros de Terapia Ocupacional, 2020)
Over the past decades, the profession of occupational therapy has increased its focus on the wellbeing of society as a whole in response to growing inequality. In addition, guidelines for occupational therapy student education have also been revised to ensure that occupational therapists graduate with an appreciation of and ability to work with diverse populations of people in multiple contexts, beyond a biomedical focus on health and impairment. As a result, occupational therapy educators have been challenged to create curricula that meet the profession’s social responsibility by preparing students to practice with communities and populations in a contextualised way. To contribute to this discussion and foster dialogue about what this may look like in occupational therapy programs, we present examples of curricula from three courses in two undergraduate occupational therapy programs in Australia and Brazil: “Understanding the Context of Occupation” and “Occupation, Health and Participation - Communities and Populations”, at Griffith University, Australia; and the course “Social Occupational Therapy”, at the Federal University of Sao Carlos, Brazil. The courses include topics such as: working in micro to macro contexts, working with communities and populations, collective occupation, politics and advocacy, social justice, occupational justice, social security and others. With differences across the programs, based on their geographical and institutional contexts, as well as their socio-historical and cultural contexts, the examples provide some ideas for educators about preparing students to work in a contextualised way with communities and populations.